Discrepancies Between Free Vibration of FML and Composite Cylindrical Shells Reinforced by CNTs - Masood Mohandes; Ahmad Reza Ghasemi (Mechanics of Advanced Composite Structures)
In this study, discrepancies between the free vibration of fiber-metal laminate (FML) and composite cylindrical shells reinforced by carbon nanotubes (CNTs) based on Love’s first approximation shell theory have been considered by beam modal function model. The representative volume elements consist of three and four phases for composite and FML structures, respectively, which include fiber, CNTs, polymer matrix and metal for FML cylindrical shells while the metal section is ignored for composite cylindrical shells. The modulus of carbon nanotubes reinforced composites cylindrical shell could be defined based on rule of mixture. In addition, the fiber phase can be reinforced by the obtained matrix using the extended rule of mixture. The frequencies of FML and composite cylindrical shells reinforced by CNTs have been compared to each other for different materials, lay-ups, boundary conditions, axial and circumferential wave numbers.